Alterations in plasma triglycerides lipolysis in patients with history of multifactorial chylomicronemia. (October 2017) - Marmontel, Oriane; Di Filippo, Mathilde; Marcais, Christophe; Nony, Séverine; Dumoux, Marjorie; Serveaux-Dancer, Marine; Caussy, Cyrielle; Charrière, Sybil; Moulin, Philippe
Abstract: Background and aims: The heterogeneity and mechanisms of multifactorial chylomicronemia (MCM) remain poorly understood. To gain new insights, post heparin lipolysis measured at 60 min (PHLA60), in addition to the more commonly used 10 min (PHLA10), was assessed in patients with history of MCM. Methods: 62 consecutive MCM patients were studied. The evaluation included LPL, APOC2, APOA5, GPIHBP1, LMF1 and APOE gene sequencing, as well as pre- and post-heparin injection biochemical analysis, including lipid profiles, determination of apolipoprotein B, B-48, CII, CIII, lipoprotein lipase (LPL) concentrations (LPLC0, LPLC10 and LPLC60) and post-heparin LPL activity (PHLA10 and PHLA60). Results: In controls, PHLA60 did not differ from PHLA10, while in MCM patients, PHLA60 was significantly lower than PHLA10 ( p <0.001). PHLA60 showed a bimodal distribution in MCM patients ( p =0.03). One subgroup exhibited PHLA60 similar to controls, with persistent lipoprotein remodeling and, paradoxically, the highest basal plasma TG concentration. APOE ε4 was over-represented compared to the European population ( p <0.05) and Apo CIII/Apo B ratio was increased ( p <0.01). The other subgroup exhibited low PHLA60 ( p <0.001) compared to both controls and the other MCM subgroup with a lipoprotein profile consistent with fast and transient remodeling. LMF1 p. Arg364Gln was over-represented compared to the European population ( p <0.05). Conclusions: The study showed that PHLA60 identifies a subgroup of MCM with a defect in lipolysability and/or hepatic clearance of triglycerides-rich lipoproteins, and a larger one with a defect in LPL availability. These findings provide new insights into the heterogeneity of MCM and might contribute to adjust treatment targeting. Highlights: Low pre heparin LPL concentration in multifactorial chylomicronemia (MCM) patients. Normal post heparin LPL activity (PHLA) at t10 in MCM patients. Decreased PHLA at t60 in a specific subset of MCM patients. These results support different pathologic pathways in MCM patients.